1994
DOI: 10.1128/jb.176.12.3598-3605.1994
|View full text |Cite
|
Sign up to set email alerts
|

Role of the FliA-FlgM regulatory system on the transcriptional control of the flagellar regulon and flagellar formation in Salmonella typhimurium

Abstract: In the flagellar regulon of Salnonella typhimurium, the flagellar operons are divided into three classes, 1, 2, and 3, with respect to transcriptional hierarchy. The class 2 operons are controlled positively by the class 1 genes,flhD andflhC. The class 3 operons are controlled positively byfliA and negatively byflgM. It has been shown that FliA is a sigma factor specific for class 3, whereas FlgM is an anti-sigma factor which binds FliA to prevent its association with RNA polymerase core enzyme. Therefore, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
159
3
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(169 citation statements)
references
References 28 publications
6
159
3
1
Order By: Relevance
“…DNase I footprinting analysis revealed the FlhD/FlhC-binding sites 30 to 80 bp upstream of the transcriptional start sites (Liu and Matsumura, 1994). In all class 2 operons of Salmonella, FlhD/FlhC-dependent transcription was shown in vivo to be enhanced by the flgM mutation in the presence of a functional fliA operon (Kutsukake and Iino, 1994). Though some of the class 2 operons have been shown to contain σ 28 -dependent promoters in addition to class 2 promoters (Liu and Matsumura, 1996), most of the class 2 operons lack σ 28 -dependent promoters (Ikebe et al, 1999b).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…DNase I footprinting analysis revealed the FlhD/FlhC-binding sites 30 to 80 bp upstream of the transcriptional start sites (Liu and Matsumura, 1994). In all class 2 operons of Salmonella, FlhD/FlhC-dependent transcription was shown in vivo to be enhanced by the flgM mutation in the presence of a functional fliA operon (Kutsukake and Iino, 1994). Though some of the class 2 operons have been shown to contain σ 28 -dependent promoters in addition to class 2 promoters (Liu and Matsumura, 1996), most of the class 2 operons lack σ 28 -dependent promoters (Ikebe et al, 1999b).…”
mentioning
confidence: 99%
“…We previously showed that enhancement of class 2 Ikebe et al (1999a) expression by the flgM mutation is cancelled by the fliA::Tn10 mutation (Kutsukake and Iino, 1994). However, because the fliA operon was later found to contain the fliZ gene (Fig.1), the fliA strain we had used should not express the fliZ gene efficiently owing to a polar effect of the Tn10 insertion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, simulations of our model in a DflgM mutant leads to elimination of the lag in expression of class 3 genes. In a HBB mutant, since no secretion is possible, class 3 expression is eliminated (Kutsukake and Iino 1994). However, there is no significant impact on class 2 gene expression.…”
Section: Hierarchical Expression Of Class 2 and Class 3 Genes In Flagmentioning
confidence: 99%
“…The flagellar operons are organized as a hierarchy within the regulon, with the expression of operons at a given level affecting the expression of operons at lower levels (20,24). The flhDC operon lies on the top of the hierarchy as the sole class I operon, with both of its gene products being absolutely required for the expression of all other genes of the flagellar regulon (15), i.e., those belonging to the class II and III operons.…”
Section: Discussionmentioning
confidence: 99%